Ji qi xue xi she ji mo shi = Machine learning design patterns - Lakshmanan, Valliappa; Robinson, Sara; Munn, Michael (ML solutions engineer) (Dong nan da xue chu ban she = Southeast University Press, 2022)
Detailed summary in vernacular field.